Evaluasi Layanan E-Learning Menggunakan Framework Cobit 5 Domain MEA dan EDM - Siti Indriane Maebari; Syafrianto (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
Technology can be said to be the key to support and improve company management. One method of managing information technology that is widely used is IT governance which is contained in COBIT. The device used is the COBIT framework provided by ISACA. Audit of e-learning service evaluation information systems at the Cibinong Representative Syifa Budi Foundation. The measurement in question is whether it is running well or not, the authors use an approach using the COBIT 5 Domain MEA and EDM framework with the COBIT 5, it can be concluded that the evaluation of e-learning services which had not been audited before, after there was research, it has reached the expected target and level. The results obtained from the calculation of the questionnaire data processing when viewed from the rating scale are included in level F that is, it has achieved a Fully achieved value and from the rounding scale the capability model condition mapping index is at level 4, namely Predictable Process, where the average data value of each sub domain, EDM 01 sub-domain manturity level is 996% and MEA 01 manturity level is 952%, has been successful implemented and has achieved the goals planned by the company